Defining a geographically weighted regression model of urban evolution. Application to the city of Volos, Greece - Kerasia Milaka; Yorgos Photis (European Regional Science Association (ERSA), 2004)
The main objective of this paper is the multivariate analysis of urban space and specifically with the use of data that refer to the level of city block. Part of the analysis has been the comparative assessment of multiple linear regression and geographically weighted regression (GWR) analysis as well as the application of the aforementioned methods in the study of the central district of the Volos metropolitan area. The city of Volos is an urban conglomeration of approximately 110.000 inhabitants, located at the middle-east of Greece and is considered to be in the upper extreme in the cities' urban hierarchy in Greece. The results provide a response to a question raised by spatial scientists during the last decades: is there a way that regression analysis can reveal spatial variations of results and with respect to scale fluctuation? The use of classical multiple regression analysis provides a single result – equation for the entire area. On the other hand, geographically weighted regression analysis stems from the fact that the above result is inadequate to reflect the different relational levels among selected variables characterizing the entire area. New estimations with the use of GWR declare the existence of various sub-areas – divisions of the initial territory – formulating a set of equations that reveal the spatial variations of variable relations. The results of the application have well proved the dominance of the analysis in the local level towards the analysis in the global level, highlighting the existence of intense spatial differentiations of variables that “interpret” the rate of land values in the city. Moreover, the distinct spatial patterns that emerge throughout the entire area, establish an alternative approach of urban spatial phenomena interpretation and a new explanatory basis for the clarification of obscure relations.
Keywords: 330